A clinical trial on the effectiveness of MERITA group therapy for emotion regulation and interpersonal skills in children and adolescents exposed to abuse and domestic violence - Mar Alvarez-Segura; Anna Butjosa; María Angeles Navarro; Eva María Ortiz-Jiménez; Teresa Richart; Paola De Rose; Veronica Sperandini; Fernando Lacasa (Academia Mental Health & Well-Being)
Few studies have examined the effectiveness of group therapy for PTSD in witnesses of domestic violence (WDV). The aim of this clinical trial was, firstly, to assess the effectiveness of a manualized emotional regulation and interpersonal abilities group therapy (MERITA) for child and adolescent WDV treated at the center (TAU); and secondly, to analyze the differences (MERITA + TAU vs. TAU) in traumatic, depressive, and anxious symptomatology, emotional dysregulation, interpersonal difficulties, externalizing and internalizing symptoms, somatic complaints, prosocial behavior, attachment, and family functioning. A total of 128 WDV patients were required (64 for the intervention group and 64 for the control group) from the Child and Adolescent Mental Health Center (Cornellà de Llobregat, Barcelona, Spain) of the Hospital Sant Joan de Déu. Specifically, MERITA + TAU was compared to TAU (post-trial and at 3-month follow-up). Furthermore, in the MERITA + TAU group (intervention group), the temporal evolution of the measures was analyzed. Statistical analyses were carried out, using a linear mixed model with pre-, post-, and 3-month follow-up measurements, where the temporal evolution of the measurements and the differences in the results according to the group (MERITA + TAU/TAU) were studied. In addition, a mixed linear model with measurements was used before, after, and at 3-, 6-, and 12-month follow-up with MERITA + TAU to evaluate the temporal evolution of the measurements. The structure of the MERITA protocol and the rigorous design based on the SPIRIT methodology and the CONSORT guidelines made it an optimal protocol for conducting a clinical trial. Trial registration: NCT05917730 (date of registration: 2020 Oct 1).